The Experience Economy and Marketing Approach in Rural Tourism that Creates Memorable Experience (A Study in Cikolelet Tourism Village) - Juliana; Sabrina Oktaria Sihombing; Ferdi Antonio (Ilomata International Journal of Social Science, 2023)
The approach and use of the experience economy has transformed a tourist village with new added value. The presence of ecotourism-based tourism villages and examines the use of community-based tourism models in the development of tourism villages. Through the CBT model, the development of tourist villages has an impact on reducing unemployment, being able to maintain local wisdom and encouraging village independence. The research objective is to examine the use of the experience economy and the use of the CBT model in the development of the Cikolelet tourism village. The research method uses qualitative research methods. Informants in the study were the head of the tourism village Pokdarwis and member of Pokdarwis of the Cikolelet tourism village who understood tourism villages. Data collection techniques were carried out through observations, interviews, and direct documentation of the research object. The results of the study can be concluded that The experience economy concept can be applied to Cikolelet rural tourism to enhance the tourist experience and create a unique and memorable destination. The experience economy is based on the idea that people are increasingly seeking experiences over material goods, and that businesses can create value by designing and delivering unique and memorable experiences.